Primary care‐based screening for cardiovascular risk factors in patients with psoriasis3. (12th July 2016) - Rutter, M.K.; Kane, K.; Lunt, M.; Cordingley, L.; Littlewood, A.; Young, H.S.; Chew‐Graham, C.A.; Hilton, R.; Symmons, D.P.M.; Griffiths, C.E.M.
Summary: Background: Studies assessing cardiovascular disease (CVD) risk factors in patients with psoriasis have been limited by selection bias, inappropriate controls or a reliance on data collected for clinical reasons. Objectives: To investigate whether screening for CVD risk factors in patients with psoriasis in primary care augments the known prevalence of CVD risk factors in a cross‐sectional study. Methods: Patients listed as having psoriasis in primary care were recruited, screened and risk assessed by QRISK2. Results: In total, 287 patients attended (mean age 53 years, 57% women, 94% white British, 22% severe disease, 33% self‐reported psoriatic arthritis). The proportion with known and screen‐detected (previously unknown) risk factors was as follows: hypertension 35% known and 13% screen‐detected; hypercholesterolaemia 32% and 37%; diabetes 6·6% and 3·1% and chronic kidney disease 1·1% and 4·5%. At least one screen‐detected risk factor was found in 48% and two or more risk factors were found in 21% of patients. One in three patients (37%) not previously known to be at high risk were found to have a high (> 10%) 10‐year CVD risk. Among the participants receiving treatment for known CVD risk factors, nearly half had suboptimal levels for blood pressure (46%) and cholesterol (46%). Conclusions: Cardiovascular risk factor screening of primary care‐based adults with psoriasis identified a high proportion of patients (i) at high CVD risk, (ii) with screen‐detected risk factors and (iii) with suboptimally managed known risk factors. These findings need to be considered alongside reports that detected limited responses of clinicians to identified risk factors before universal CVD screening can be recommended. Abstract : What's already known about this topic? Several studies have suggested that patients with psoriasis have a greater number of risk factors for cardiovascular disease (CVD) and a higher risk for vascular events compared with the general population. However, the prevalence data used to support systematic CVD risk factor screening in psoriasis have been limited by selection bias, inappropriate choice of control groups or reliance on risk factors measured for other clinical reasons. What does this study add? Cardiovascular risk factor screening of primary care‐based adults with psoriasis identified a high proportion of patients (i) at high CVD risk, (ii) with screen‐detected risk factors and (iii) with suboptimally managed known risk factors. These findings need to be considered alongside reports that detected limited responses of clinicians to identified risk factors before universal CVD screening can be recommended. Plain language summary available online